The Crystallographic Texture in The Medium Carbon Steel Wires: From The EBSD to The OIMTM Analysis Software - Nebbar, Mohamed Chaouki; Zidani Mosbah; Djimaoui Toufik; Baudin Thiery (University Of Eloued جامعة الوادي, 2020)
This study falls within the framework of a scientific collaboration with the national wire drawing and manufacturing company of welding products TREFISOUD JSC, specialized in the manufacturing of long type steel products. The TREFISOUD today offers a varied range of solutions for different sectors such as industry, agriculture, construction and public works. Indeed, whether it is drawn wires, steels for the manufacture of mattress springs, strand cables and welding products. The company covers a wide variety of applications through the production of drawn wires by single-pass and multi-pass type machines The medium-carbon steel is mong steels of wide use. During this study, a medium-carbon steel wires produced by the national drawing and welding products manufacturing company (Algeria) was characterized by two analytical techniques. One is scanning electron microscopy (SEM) to monitor the microstructure evolution and the second is electron back scatter diffraction (EBSD) for the crystallographic texture analysis. The EBSD results are processed with OIM (Orientation Imaging Microscopy) analysis software.
Intervention
Keywords: Medium-carbon steel; Wire drawing; Microstructure; Texture; OIM Analysis